How digitalization drives the IT/IS strategy agenda - Jan Stockhinger; Alexander Teubner (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2019)
Through out the last decade, digitalization has fundamentally transformed the business world and put into question traditional strategy wisdom. As (digital) information technologies (IT) are the drivers of this transformation, we can expect it to have an even more profound influence on IT/IS strategy thinking. While several scholars have acknowledged the fundamental changes induced by digitalization on the conceptual level, research on emerging IT/IS strategy contents is still missing. This paper intends to fill this gap by revealing both practically relevant and theoretically valid concerns worth considering when developing IT/IS strategies for/in the digital age. Based on a working definition of digitalization, we present a set of hypotheses on how IT/IS strategies might respond to trends in digitalization. We also put these hypotheses to discussionin ten interviews with IT/IS managers in practice. Our research adds to a better understanding of the complex phenomenon of digitalization and its implications for IT/IS strategy development. Our research responds to calls for a stronger focus on strategy contents and more practice-oriented IT/IS strategy research.
Keywords: 650; Digitalization; digital transformation; IT/IS strategy; information infrastructure strategy; information function strategy; IT/IS strategy contents